Development of Thermoplastic 3D Woven Composite - Kang , Chin Ann (IRC, 2020)
There is a growing concern over the recycling issue of thermosetting composite and the weakness of 2D composite in resisting out-of-plane load in composite manufacturing industry. In this paper, the effect of the off-axis angle on the flexural behaviours of thermosetting and thermoplastic three-dimensional woven composites will be presented and the suitability of thermoplastic 3D woven composite as a substituent for thermosetting 3D woven composite will be assessed. Three-point bending test is employed to test six kinds of samples made of thermoplastics and thermosetting resins at 0 degree,45 degree and 90 degree. Visual inspection is carried out on the damaged samples to characterise the macro-scale damage of 3D woven composite fractured in bending.